Records and descriptions of some Aphelinidae (Hymenoptera: Chalcidoidea) from India - Hayat, Mohammad (Zootaxa, 2012)
Two new species, Centrodora flemingiae Hayat, sp. nov. and Proaphelinoides assamensis Hayat, sp. nov. (Hymenoptera: Aphelinidae), are described. The latter species is described for an Indian specimen earlier misidentified as P. australis Girault. Also, the following five species are recorded: Coccophagus fumadus Hayat, C. longifasciatus Howard, C. zebratus Howard, Eriaphytis chackoi Subba Rao and Paraphytis transversa (Huang). Coccophagus zebratus and Paraphytis transversa are redescribed because these two species are newly recorded from India.